An equilibrium model for linear and closed-loop amyloid fibril formation - Yang, Shuo (2012)
Amyloid fibrils and their soluble oligomeric intermediates are implicated in several age-related diseases including Alzheimer’s and Parkinson’s disease. The distribution of oligomers and fibrils is related to toxicity and is dependent on the pathways for fibril assembly, generally considered to occur via a slow nucleation step that precedes fibril elongation. Human apolipoprotein (apo) C-II forms amyloid fibrils via a reversible self-assembly process accompanied by closed-loop formation and fibril breaking and joining. Our fluorescence quenching and sedimentation velocity experiments with Alexa488-labelled apoC-II indicated a time-dependent sub-unit interchange for both linear and closed-loop fibrils, while dilution experiments using mature fibrils indicated a shift to smaller size distributions consistent with a reversible assembly pathway. To account for this behaviour we developed an equilibrium self-association model that describes the final size distributions of apoC-II fibrils formed at different starting concentrations. The model proposes a reversible isomerisation of apoC-II monomer to form an active conformer that self-assembles into fibrils via an isodesmic self-association pathway coupled to fibril length-dependent closed-loop formation. The model adequately described fibril size distributions and the proportion of closed-loops as a function of total apoC-II concentration over the concentration range 0.1–0.5 mg/ml. Extension of the model to include the rates of isomerisation, self-association and fibril breaking and joining provided satisfactory global fits to kinetic data on fibril formation and changes in average fibril size at different apoC-II starting concentrations. The model provides a simple thermodynamic description of the processes governing the size distribution of apoC-II fibrils at equilibrium and the formation of discrete oligomeric intermediates.